2019
DOI: 10.1002/adem.201901311
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characterization of Mechanically Alloyed FeCoNiMnV High Entropy Alloy Consolidated by Spark Plasma Sintering

Abstract: The microstructure and phase evolution of the mechanically alloyed FeCoNiMnV high entropy alloy during spark plasma sintering are examined. The milled powders are sintered at different temperatures ranging between 500 C and 1000 C. A multiphase structure is produced during the sintering process. The produced alloy experiences different types of decompositions and phase formations as the sintering temperature is raised. During sintering at different temperatures, the body centered cubic and face centered cubic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(153 reference statements)
0
2
0
Order By: Relevance
“…The presence of a small amount of V‐Mn precipitates, which are identified as σ phases, is also demonstrated in the following microstructure images ( Figure ) and SEM elemental maps ( Figure ) of CoFeNiMnV HEAs. [ 48 ] However, due to the relatively small content of the σ phase, the diffraction peaks of the σ phase could not be detected by XRD.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a small amount of V‐Mn precipitates, which are identified as σ phases, is also demonstrated in the following microstructure images ( Figure ) and SEM elemental maps ( Figure ) of CoFeNiMnV HEAs. [ 48 ] However, due to the relatively small content of the σ phase, the diffraction peaks of the σ phase could not be detected by XRD.…”
Section: Resultsmentioning
confidence: 99%
“…The role of contaminants during MA-SPS of HEAs has also been exemplified in literature (although the thermodynamic explanations using G-x plots have never been discussed). The quinary CoFeMnNiV alloy is reported to have σ-phase after MA and SPS, in which C or O contamination is avoided [33,34]. Praveen et al [22] have demonstrated that the unsolicited C addition during MA-SPS provides excellent phase stability and very high hardness to AlCoCrFe due to the formation of M 23 C 6 carbides.…”
Section: Absence Of σ-Phase After Ma-sps Of Cocrfemnniva Kinetic Pers...mentioning
confidence: 99%